2015
DOI: 10.1111/aor.12464
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Coagulation Parameters, Anticoagulation, and Need for Transfusion in Patients on Interventional Lung Assist or Veno-Venous Extracorporeal Membrane Oxygenation

Abstract: Clinical data on anticoagulation needs of modern extracorporeal membrane oxygenation (ECMO) and its impact on coagulation are scarce. Therefore, we analyzed coagulation-related parameters, need for transfusion, and management of anticoagulation in adult patients with severe acute respiratory failure during treatment with either pumpless interventional lung assist (iLA) or veno-venous ECMO (vv-ECMO). Sixty-three patients treated with iLA and 192 patients treated with vv-ECMO at Regensburg University Hospital be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
4
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 39 publications
3
41
4
3
Order By: Relevance
“…This could be related to blood–surface interactions or clotting within the ECMO device. However, D‐dimer and fibrinogen levels evolved in the direction opposite to that of coagulopathy, in contrast to the results of Weingart et al . Although we had few patients, this might be attributable to the anticoagulation agents used in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…This could be related to blood–surface interactions or clotting within the ECMO device. However, D‐dimer and fibrinogen levels evolved in the direction opposite to that of coagulopathy, in contrast to the results of Weingart et al . Although we had few patients, this might be attributable to the anticoagulation agents used in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…There are several reasons why our findings contradict two prior cohort studies that concluded that platelets counts decline with ECMO use [13, 22]. In a cohort study of 225 adults with severe ARDS who were supported with either venovenous ECMO or pumpless arteriovenous interventional Lung Assist (iLA), platelet counts decreased significantly in those who received ECMO but not in those who received iLA.…”
Section: Discussioncontrasting
confidence: 92%
“…The potential platelet-reducing effect of ECMO therapy is clinically important since ECMO patients who develop thrombocytopenia may have an increased risk of bleeding [10]. Two recent single-center cohort studies examined the association between ECMO use and the development of thrombocytopenia among adults with acute respiratory failure [13, 22]. While both studies report a significant decline in platelet count over days on ECMO, neither controlled for potential confounding factors including subjects' severity of illness or the duration of ECMO therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the current data do not allow conclusions on this issue. Thrombocytopenia, on the other hand, is one of the many complications of ECMO [48][49][50]. It is estimated that approximately 1 in 5 patients may experience severe thrombocytopenia (platelets < 50 × 109/L) [48].…”
Section: Laboratory Disorders In Sars-cov-2 Infection Vs V-v Ecmomentioning
confidence: 99%